Nursing care to patient with abdominal aortic aneurysm in relation to a type of treatment and hospitalization mode - Piotrkowska, Renata; Terech, Sylwia; Książek, Janina (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. The aim of the study was to compare the range of request for nursing care in patients with abdominal aortic aneurism treated either by traditional or endovascular surgical methods, based on individual case study. Material and methods. The research was conducted in one of Tri-city hospitals, in the Vascular Surgery Department. The material comprised two patients treated surgically by two techniques: traditional and endovascular. The methods used in the research included: observation, medical records analysis, case analysis, nursing care process analysis and interview. Results. The patient treated by the traditional surgery required fully compensatory nursing care in early post-operative period. In the patient treated by the endovascular surgery, the system of care applied was partially compensatory and teaching-supportive.s Conclusions. Application of a specific method in the treatment of abdominal aortic aneurism (in the cases described) had an impact of the scope of nursing care required, especially in the post-operative period. Regardless of the treatment method, the patients require close observation and the main goal of nursing care is ensuring their safety and comfort.